2013
DOI: 10.1155/2013/301982
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress and Nucleic Acid Oxidation in Patients with Chronic Kidney Disease

Abstract: Patients with chronic kidney disease (CKD) have high cardiovascular mortality and morbidity and a high risk for developing malignancy. Excessive oxidative stress is thought to play a major role in elevating these risks by increasing oxidative nucleic acid damage. Oxidative stress results from an imbalance between reactive oxygen/nitrogen species (RONS) production and antioxidant defense mechanisms and can cause vascular and tissue injuries as well as nucleic acid damage in CKD patients. The increased productio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
110
2
7

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(125 citation statements)
references
References 146 publications
3
110
2
7
Order By: Relevance
“…Nephritis has tendancy to induce oxidative stress via inflammation [31] which also is a characteristic feature of SLE [9]. Oxidative stress has also been observed also in the present case.…”
Section: Discussionsupporting
confidence: 77%
“…Nephritis has tendancy to induce oxidative stress via inflammation [31] which also is a characteristic feature of SLE [9]. Oxidative stress has also been observed also in the present case.…”
Section: Discussionsupporting
confidence: 77%
“…However, in recent years, many studies have shown that their metabolites are involved in the progression of kidney disease. Creatinine is converted to creatinine hydroxide in the presence of free radicals, 13 eventually generating methylguanidine which is more toxic, 14 which increases the expression of TGF-b1, CTGF and FN in renal tubular epithelial cells and exacerbates renal tubular interstitial fibrosis. 15 In this way, creatinine indirectly promotes fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…5 A vitamina B12 é essencial em diversas reações bioquímicas do organismo que implicam na dinâmica de redistribuição de elementos como o hidrogênio e carbono. 6 Já o ácido fólico tem um papel importante na prevenção da incorporação de uracil ao DNA e na sua metilação, atuando na estabilidade genômica juntamente com outros micronutrientes.…”
Section: Introductionunclassified
“…Derivam da ruptura cromossômica causada por lesões ao DNA não reparadas ou mal reparadas, ou, ainda, da segregação incorreta na anáfase. 5 Além dos MN, outras alterações nucleares envolvem as evidências de dano ao genoma das células analisadas. As primeiras alterações genômicas implicam na organização nuclear e se manifestam como alterações em seu tamanho, em sua densidade e na distribuição de sua cromatina.…”
Section: Introductionunclassified